Comparação do volume de tecido dental removido no acesso endodôntico guiado e convencional em incisivos inferiores - Elias, Marcela Ramos Abrahão (2019)
Aim: To compare the volume of dental tissue removed in conventional and minimally invasive endodontic access with the use of prototyped endodontic guides, in extracted human mandibular incisors. Materials and methods: Twenty extracted healthy human mandibular incisors were submitted to the cone beam computed tomography (CBCT) exam before and after endodontic access. The teeth were divided into two groups, according to the type of access: group 1 (G1) conventional access (n = 10) and group 2 (G2) minimally invasive access (n = 10). For G2, prototyped guides were made in 3D printer through the association of the image of the CBCT with the digital scanning of the teeth. The evaluation of the volume of dental tissue was performed by transferring the images in the DICOM format to the InVesalius® software, in which three-dimensional (3D) reconstruction of tomography sections was performed. Based on the initial volume (Vi) and final volume (Vf), the volume of tissue removed (Vr) was calculated by the formula: Vr = Vi - Vf. Results: There was no difference in Vi (p = 0.589) and Vf comparisons (p = 0.724) between groups. The mean dental volume removed at the conventional access and minimally invasive were respectively 31.677 mm 3 and 26.523 mm 3 . There was a mean volume reduction of 10.62% in the conventional access and 10.65% in the minimally invasive access, with no significant difference between the groups (p = 0.960). Conclusion: There was no significant difference in the volume of dental tissue removed when compared to conventional and minimally invasive endodontic access in extracted human mandibular incisors.